Features of the application of electromagnetic bioresonant therapy of inflammatory infectious diseases - Vladimir Grunskiy; Sergey Kalmykov; Yuliya Kalmykova (Kharkiv State Academy of Physical Culture, 2019)
Purpose: to develop an apparatus and method for electromagnetic bioresonance therapy of inflammatory infectious diseases. Material & Methods: analysis of scientific and medical literature and information sources on the coverage of the influence of electromagnetic fields on biological objects, systematization and generalization of the results on the research topic. Results: an apparatus and method for electromagnetic bioresonance therapy with the determination of the frequency of natural vibrations of the causative agents of the disease with the subsequent generation of forced pulses by the magnitude of their frequency, which coincides with the bioresonant frequency, were developed. Conclusions: the determination of the frequency of natural oscillations of the causative agents of the disease and the further generation of forced pulses by the magnitude of their frequency, which coincides with the bioresonant frequency, significantly increases the therapeutic effect of treatment and at the same time reduces the duration of each cycle of action of the forcedly generated pulses, as well as the total time of treatment of the disease.